PDZ-domain interactions and apical expression of type IIa Na/P(i) cotransporters - Hernando, Nati (The National Academy of Sciences, 2002)
Type IIa Na/P(i) cotransporters are expressed in renal proximal brush border and are the major determinants of inorganic phosphate (P(i)) reabsorption. Their carboxyl-terminal tail contains information for apical expression, and interacts by means of its three terminal amino acids with several PSD95/DglA/ZO-1-like domain (PDZ)-containing proteins. Two of these proteins, NaPi-Cap1 and Na/H exchanger-regulatory factor 1 (NHERF1), colocalize with the cotransporter in the proximal brush border. We used opossum kidney cells to test the hypothesis of a potential role of PDZ-interactions on the apical expression of the cotransporter. We found that opossum kidney cells contain NaPi-Cap1 and NHERF1 mRNAs. For NHERF1, an apical location of the protein could be documented; this location probably reflects interaction with the cytoskeleton by means of the MERM-binding domain. Overexpression of PDZ domains involved in interaction with the cotransporter (PDZ-1/NHERF1 and PDZ-3/NaPi-Cap1) had a dominant–negative effect, disturbing the apical expression of the cotransporter without affecting the actin cytoskeleton or the basolateral expression of Na/K-ATPase. These data suggest an involvement of PDZ-interactions on the apical expression of type IIa cotransporters.